Protective Effects of Live Combined B. subtilis and E. faecium in Polymicrobial Sepsis Through Modulating Activation and Transformation of Macrophages and Mast Cells - Guo, Lisha; Meng, Mei; Wei, Yaping; Lin, Feixue; Jiang, Ying; Cui, Xianzhen; Wang, Guirong; Wang, Chunting; Guo, Xiaosun (Frontiers in Pharmacology, 2019)
Aims:Clinical studies demonstrate that the treatment with probiotics in critical illness could reduce nosocomial infection and improve clinical outcome. The functional mechanisms of probiotics is unclear yet. This study aims to explore the mechanistic effects of live combined Bacillus subtilis and Enterococcus faecium (LCBE) in cecal ligation puncture (CLP)-induced sepsis. Methods and results:Seven week-old C57BL/6J mice were divided into 3 groups: Sham group, CLP-control (pretreatment with Saline for 7 days before CLP surgery) and CLP-probiotics group (pretreatment with LCBE enteric-coated capsules for 7 days before CLP). For survival study animals were monitored for 7 days after CLP. For other studies mice were sacrificed three days after Surgery, and then serum, ileum tissues and peritoneal lavage fluid were collected for various analyses. The results showed that the mortality rate was significantly reduced in CLP-probiotics as compared to CLP-control (P<0.05). The pathological changes of ileum tissues in CLP-probiotics were attenuated compared with CLP-control (P<0.05). The IL-6 and TNF-α levels in the serum and ileum tissues in CLP-probiotics were lower than CLP-control. No differences of IL-10 and TGF-β1 were observed between CLP-control and CLP-probiotics. Furthermore, we found that probiotics could exert suppressing the macrophage activation and transformation from M-type to M1-type, and reducing degranulation of mast cells (MCs), as well as promoting the activation of AKT (kinase B) pathway. Conclusion:Thus, our data first time provide the mechanistic effects of probiotics in mouse CLP sepsis through reducing ileum tissue inflammation, altering macrophage polarization and MCs degranulation, and regulating AKT signaling. Significance and Impact of Study: This study demonstrated the clinical effect of live combined Bacillus subtilis and Enterococcus faecium (LCBE) in cecal ligation puncture (CLP)-induced sepsis.